Porcine IFI16 Negatively Regulates cGAS Signaling Through the Restriction of DNA Binding and Stimulation - Zheng, Wanglong; Zhou, Rongyun; Li, Shuangjie; He, Shan; Luo, Jia; Zhu, Meiqin; Chen, Nanhua; Chen, Hongjun; Meurens, François; Zhu, Jianzhong (Frontiers in Immunology, 2020)
The innate immunity DNA sensors have drawn much attention due to their significant importance against the infections with DNA viruses and intracellular bacteria. Among the multiple DNA sensors, IFI16 and cGAS are the two major ones, subjected to extensive studies. However, these two DNA sensors in livestock animals have not been well defined. Here, we studied the porcine IFI16 and cGAS, and their mutual relationship. We found that both enable STING dependent signaling to downstream IFN upon DNA transfection and HSV-1 infection; and cGAS plays a major role in DNA signaling. In terms of their relationship, IFI16 appeared to interfere with cGAS signaling as deduced from both transfected and knockout cells. Mechanistically, IFI16 competitively binds with agonist DNA and signaling adaptor STING, thereby influences second messenger cGAMP production and downstream gene transcription. Furthermore, the HIN2 domain of porcine IFI16 harbored most of its activity and mediated cGAS inhibition. Thus, this study provides a unique insight of porcine DNA sensing system.